PERANAN KPOP IDOL BTS (BANGTAN BOYS) DALAM PROGRAM GENERATION UNLIMITED - Ananda, Ridha; Iskandar, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to explain how the role of K-Pop idol BTS in the Generation Unlimited program. The UN in particular UNICEF is collaborating with a Korean music group that is at the peak of its fame namely BTS in the Generation Unlimited program. A program that focuses on supporting youth in building self-confidence, nonviolent advocacy, education, training and support to overcome the problems of the youth phase. This study raises the problem of the role of BTS in the continuation of Generation Unlimited. This research method was obtained from books, journals, and websites that support the hypothesis. In this paper, the author uses Constructivism perspective with soft diplomacy. The author uses the level of group analysis as an actor in international relations. This research uses qualitative research methods.   The results of this study include BTS participating in the UNICEF program before Generation Unlimted, BTS Speeches at the 2018 annual UN general assembly in New York, BTS Album titled 'Love Myself', BTS campaign titled 'Love Myself' and distribution of BTS funds for various school in the world. Keywords: Role, UNICEF, K-Pop Idol, BTS Generation Unlimited, campaign, teenagers.